Beckman enzyme detector (1976)
Under contract to the U.S. Army Mobility Equipment Research and Development Center, Beckman's Microbics and Advanced Technology Operations worked to develop an enzymatic vapor detector.
Keywords: United States. Army; Enzymes--Analysis; Beckman Instruments, Inc.; Scientific apparatus and instruments